2018
DOI: 10.1002/phar.2163
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Off‐Target Serotoninergic Drug Activity: An Analysis of Serotonin Syndrome Reports Using a Systematic Bioinformatics Approach

Abstract: Study Objective Serotonergic adverse drug events (ADEs) are caused by enhanced intra-synaptic concentrations of 5-hydroxytryptamine (5-HT). No systematic process currently exists for evaluating cumulative 5-HT and off-target toxicity of serotonergic drugs. The primary study aim was to create a Serotonergic Expanded Bioactivity Matrix (SEBM) employing a molecular bioinformatics, poly-pharmacologic approach for assessing the participation of individual 5-HT drugs in serotonin syndrome (SS) reports. Data Source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 37 publications
1
25
0
4
Order By: Relevance
“…Analysis of the FDA Adverse Event Reporting System (FAERS) of serotonin syndrome cases by our group suggests that the two criteria differ substantially in their clinical application. This was evident from an additional 1100 FAERS cases identified by Sternbach but not Hunter's criteria 4 . Thus, Sternbach's inclusion of more nonspecific symptoms may result in identification of milder toxicity cases.…”
Section: Severe Versus Mild Serotonin Toxicitymentioning
confidence: 96%
See 3 more Smart Citations
“…Analysis of the FDA Adverse Event Reporting System (FAERS) of serotonin syndrome cases by our group suggests that the two criteria differ substantially in their clinical application. This was evident from an additional 1100 FAERS cases identified by Sternbach but not Hunter's criteria 4 . Thus, Sternbach's inclusion of more nonspecific symptoms may result in identification of milder toxicity cases.…”
Section: Severe Versus Mild Serotonin Toxicitymentioning
confidence: 96%
“…This study builds on our earlier work in which the Serotonin Expanded Biomedical Matrix (SEBM) was developed to characterize serotonergic drug interactions at 13 serotonin receptor subtypes, serotonin and norepinephrine transporter proteins, and antimuscarinic receptors 4 . An in-house bioinformatics Web service, TargetSearch (http://dxulab.org/ software) was developed to mine publicly available ChEMBL, a pharmacologic database for relevant drug-receptor interactions and functional activity 8 .…”
Section: Serotonin Receptor Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 Pharmacokinetic drug interactions are also implicated through the inhibition of the cytochrome P450 pathway, a pathway that SSRIs themselves inhibit (in particular CYP2D6 and CYP3A4. 56,57 At least 25 serotonergic drugs are metabolised by the cytochrome P450 pathway, 19 and a recent study has shown that 50% of the top 20 drugs associated with SS have known pharmacokinetic interactions in which coadministration of cytochrome P-450 inhibitors may elevate drug concentrations to toxic levels. These drugs collectively were shown to participate in > 70% of all the reported SS reports in their study.…”
Section: Drugs Commonly Associated With Ssmentioning
confidence: 99%